2019
DOI: 10.3390/ijerph16071098
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use in University Students Attending Three Superior Graduate Schools in Italy: Is Autism Spectrum Related to Suicide Risk?

Abstract: Background: Over the past decades, problematic internet use (PIU) has dramatically increased, especially among young people. PIU has been recently associated with autism spectrum disorder (ASD) and autistic traits. Subjects with PIU report an increased suicidal risk and the same has been demonstrated among patients with ASD. The aim of this study was to investigate putative PIU rates among students and explore the correlation between autistic traits and suicide risk. Methods: A sample of 178 high achieving uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…13,24,79 Moreover, we found that higher AT were associated with the presence of psychiatric disorders, as well as to a lower global functioning. This result adds to previous data, which reported high levels of AT in different kinds of psychiatric disorders, [40][41][42][43][44][45][46][47] as well as a higher frequency of psychiatric conditions in parents of subjects with ASD. 56,57 Some studies in this field ascribed the higher rates of psychopathology in parents of ASD children to the extremely stressful experience of raising a child with ASD, which may be more severe than the stress of raising a child with different kinds of disorders, such as mental retardation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…13,24,79 Moreover, we found that higher AT were associated with the presence of psychiatric disorders, as well as to a lower global functioning. This result adds to previous data, which reported high levels of AT in different kinds of psychiatric disorders, [40][41][42][43][44][45][46][47] as well as a higher frequency of psychiatric conditions in parents of subjects with ASD. 56,57 Some studies in this field ascribed the higher rates of psychopathology in parents of ASD children to the extremely stressful experience of raising a child with ASD, which may be more severe than the stress of raising a child with different kinds of disorders, such as mental retardation.…”
Section: Discussionsupporting
confidence: 82%
“…2,4 More recently, increasing literature is stressing that subthreshold autism spectrum symptoms seem to be continuously distributed in general population, and in particular in some high-risk groups, such as university students, as well as among clinical samples of patients with other psychiatric disorders, where AT are generally associated with higher severity and with increased suicide ideation and behaviors. [35][36][37][38][39][40][41][42][43][44][45][46][47] Although in literature the impact of AT in global functioning has been investigated in general population, [48][49][50][51] studies among parents of ASD children generally focused mainly on work and social adjustment related to the burden to raise a child with ASD, rather than on the functional impairment related to their own AT. 52 On the other hand, the prevalence of psychiatric conditions has been investigated also among relatives of ASD probands, highlighting an increased risk for mood disorders: one of the firsts studies in the field was led by Delong and Dwyer, 53 who found a higher rate of mood disorders in relatives of ASD children with respect to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…62 This clue is particularly interesting considering the increasing body of studies suggesting a possible role of AT as a promoting factor for different psychiatric conditions. [63][64][65][66][67][68][69][70] As Dell'Osso et al 63,71 pointed out, ruminative thinking, often associated with subthreshold AT, could be considered as a common transnosological underpinning of several different psychiatric disorders that may affect prognosis and increase the risk of chronic course and suicidality. According to this paradigm, our study may contribute in supporting the dimensional association between depressive ruminations, SAD and OCD subthreshold symptoms, considering the high correlations, found also in MDD patients and in HC, between doubt and interpersonal sensitivity.…”
Section: Cns Spectrumsmentioning
confidence: 99%
“…ATs also seem highly prevalent in a broad variety of clinical groups ( e.g. , among patients with eating disorders, mood disorders, borderline personality disorder), where they might represent a specific risk factor for suicide ideation and behaviors [26-32]. Considering the increasing number of studies which stress on the relevance of ATs in non-ASD clinical samples [33, 26-32], it has been suggested that different kinds of psychiatric conditions may be developed as a consequence of a neurodevelopmental alteration similar to the one linked to ASD; the specific localization and severity of this neurodevelopmental alteration, together with the interaction with the environment during lifetime, may lead to different psychopathological trajectories [5, 34, 35].…”
mentioning
confidence: 99%
“…This evidence raised increasing interest in the development of a more comprehensive framework, which would be able to feature cognitive, affective, and neurobiological processes shared by several psychiatric syndromes [34, 2-4]. Given the high amount of evidence about the possible role of the autism spectrum in the development of different psychiatric disorders [33, 26-32], as well as about its measurable neurobiological correlates [9, 39, 40] the autism spectrum model possibly seems to be a useful tool for this purpose.…”
mentioning
confidence: 99%